Parallel combination of FC and UC for vehicular power systems using a multi-input converter-based power interface - Vural, B.; Erdinc, O.; Uzunoglu, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Fuel cells (FC) are widely recognized as one of the most promising technologies to meet future power requirements of vehicular applications. However, a FC system combined with an energy storage system (ESS) can perform better for vehicle propulsion as considering several points. As the additional ESS can fulfill the transient power demand fluctuations, the FC system can be downsized to fit the base power demand without facing peak loads. Besides, braking energy can be recovered by the ESS. Interfacing of traction drive requirements with characteristics and modes of operation of on-board generation units and ESSs calls for suitable power electronic converter configuration. In this paper, a FC/UC hybrid vehicular power system using a multi-input converter-based power interface is proposed. The applied power interface topology ensures the active power sharing and DC link voltage stabilization for the hybrid vehicular system. The mathematical and electrical models of the hybrid vehicular system are developed in detail and simulated using MATLAB (R), Simulink (R) and SimPowerSystems (R) environments. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell; Hybrid electric vehicle; Multi-input converter; Ultra-capacitor; FUEL-CELL; CONTROL STRATEGY; HYBRID SYSTEM; MANAGEMENT; SIMULATION; DESIGN; OPTIMIZATION; BATTERIES; MULTIPLE; Thermodynamics; Energy & Fuels; Mechanics